Iron ore in Arctic Europe - Gethin, P. A. B. (Polar Record, 1959)
Iron ore in significant quantities has been found in only four areas in arctic Europe. No deposits are known in arctic Asia or in the arctic islands of the eastern hemisphere. The largest iron-bearing area is in Swedish Lapland of which the total known reserves, mainly magnetite and hematite, are estimated at 2413 million metric tons, with an average iron content of over 63 per cent, or a ferric weight of about 1532 million tons. The greater part of this ore requires no concentration before use. There is a deposit of about 1000 million tons in Sør-Varanger in north Norway, with a low iron content, while the deposit at Yena in Kol'skiy Poluostrov (Kola peninsula) is estimated at nearly 850 million tons of ore with an iron content of 23 to 48 per cent, and like the Varanger ore requires concentration. A deposit with an iron content of 30 to 40 per cent has been investigated recently at Kolari in north-west Finland, but it is not yet worked.